Cordyceps sinensis biomass produced by submerged fermentation in high-fat diet feed rats normalizes the blood lipid and the low testosterone induced by diet - Aikawa, Júlia; Bonatto, Sandro José Ribeiro; Freire dos Santos, Leandro; Habu, Sascha; Prado, Karin Braun; Rubel, Rosália; Soccol, Carlos Ricardo; Soccol, Vanete Thomaz; Torres, Maria Fernanda; Yamaguchi, Adriana Aya; Zanatta, Ana Lucia (Technische Universität Dortmund, 2013)
This study investigated the effect of Cordyceps sinensis biomass supplementation obtained from submerged fermentation on blood lipid and low testosterone induced by high-fat diet (HFD). The experiments were carried out using a long-term intake of HFD and HFD plus Simvastatin or C. sinensis (4 months). Our results show that plasma cholesterol, triglycerides and LDL were decreased by Cordyceps sinensis biomass supplementation (CSBS). A longterm intake of HFD caused a significant liver damage which has been reverted by CSBS. CSBS normalized decreasing testosterone levels observed in high-fat diet feed rats. All these findings lead us to suggest that C. sinensis was able to decrease blood lipid concentration, increase hepatoprotective activity and normalize testosterone levels.
EXCLI Journal ; Vol. 11, 2012
Keywords: Cordyceps sinensis; high-fat diet; hypolipidemic effect; testosterone; 610